Theoretical instructions for experimenting controllable Hopkinson pressure bar. (April 2022) - Miao, Yinggang; Wang, Yongshuai; Du, Wenxuan; He, He; Deng, Qiong; Dou, Qingbo
Abstract: Hopkinson bar loading technique needs theoretical instruction for desired stress waves, to achieve controllable deformation under constant high strain rate loading, for it is the indispensable access while investigating material's rate-dependence and deformation mechanism under transient loading. In this work, theoretical and experimental studies are focused on the involved issues. Firstly, the theoretical deduction based on stress wave theory is performed for constant true strain rate loading, and the equation is formulated of an ideal incident strain wave for different materials. The formulated waves are further clarified by case studies of specimens with various mechanical behaviors, and they are found to present concave characteristics under large deformation. Secondly, an efficient methodology is proposed for single stress wave loading, and the target requirement is deduced theoretically. It is easily achieved experimentally by performing specific strain-controlled experiments: prior to and beyond peak stress of epoxy. Finally, some methods are proposed for achieving the formulated stress waves, and experimental verifications are also conducted on various materials. Highlights: An ideal incident strain wave is formulated theoretically for desired constant true strain rate loading by SHPB. The waves are achieved experimentally for metal and epoxy specimen with the aid of pulse shaping technique. A succinct method is proposed for a single stress wave loading. Single stress wave loading is confirmed experimentally by performing strain-controlled experiments on epoxy.